2019
DOI: 10.21608/epsj.2019.39281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Manipulation During Incubation and Spraying Japanese Quail Eggs With Ascorbic Acid on Embryogenesis and Phsiological Responses of Hatch Chicks

Abstract: The objective of this study was to investigate the impact of spraying ascorbic acid on Japanese quail eggs submitted to high temperature during4 th to 14 th days of incubation period on embryogenesis, hatchability, embryonic mortality rate and chick quality.Six hundred Japanese quaileggs were divided into two equal groups of 300 eggs each according to incubation temperature. In the first group: eggs were incubated at 37.5°C (thermoneutral incubation temperature NIT 37.5°C)and 65% relative humidity (RH)from 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Another recent study on quail found that intermittent TM (+1.7°C, 12 h/d) during ED0‐13 improved thermotolerance during heat challenge (36°C for 7 h) at 35 days of age (Vitorino Carvalho et al, 2020). Similar to chicken but not identical, quails physiologically cope with the heat stress, with a modification of several metabolic and haematologic parameters, including an elevation in plasma corticosterone concentration and a reduction in plasma thyroid hormone levels (Abdel‐Fattah, 2019; El‐Daly et al, 2013; Porto & Fontenele‐Neto, 2020; Vitorino Carvalho et al, 2020). Correspondingly, the surface temperature of the shank was decreased, suggesting a modulation of the blood flow to sustain the interior temperature.…”
Section: Effects Of Embryonic Thermal Manipulation On Thermotolerance...mentioning
confidence: 99%
“…Another recent study on quail found that intermittent TM (+1.7°C, 12 h/d) during ED0‐13 improved thermotolerance during heat challenge (36°C for 7 h) at 35 days of age (Vitorino Carvalho et al, 2020). Similar to chicken but not identical, quails physiologically cope with the heat stress, with a modification of several metabolic and haematologic parameters, including an elevation in plasma corticosterone concentration and a reduction in plasma thyroid hormone levels (Abdel‐Fattah, 2019; El‐Daly et al, 2013; Porto & Fontenele‐Neto, 2020; Vitorino Carvalho et al, 2020). Correspondingly, the surface temperature of the shank was decreased, suggesting a modulation of the blood flow to sustain the interior temperature.…”
Section: Effects Of Embryonic Thermal Manipulation On Thermotolerance...mentioning
confidence: 99%